Prenatal Covid-19 on Toddler Development - Pasongli, Seri; Budu, Budu; Ahmad, Mardiana; Prihantono, Prihantono; Hidayanti, Healthy; Arsyad, M. Aryadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Along with the spread of the COVID-19 pandemic, there has been an increase in reports of confirmed cases of pregnant women with COVID-19. Exposure to the virus in pregnancy can affect the fetus and result in long-term vulnerability to abnormalities in the child's brain development. This study aimed to determine the impact of prenatal Covid-19 on the development of toddlers. The research method uses observational cross-sectional analysis. Secondary data on confirmed Covid-19 mothers were obtained from Prof. RD Kandou General Hospital, Wolter Monginsidi Hospital, and Manado Adventist Hospital. Primary data on toddler development using the KPSP Development Questionnaire instrument were obtained from 10 Community Health Centers in Manado City with a total of 92 respondents for two, 46 respondents were born to mothers with Covid-19 during the prenatal period and 46 toddlers were born to mothers who were not confirmed to have Covid-19 during the prenatal period. The results showed that there was no significant effect with a p-value of 0.562 for toddlers born to Covid-19 mothers on impaired gross motor, fine motor, socialization, and independence, speech, and language development. Based on the results of the study it can be concluded that both toddlers born to Covid-19 mothers and toddlers who were not born to Covid-19 mothers are at risk of experiencing growth disturbances, especially toddlers born during the Covid-19 pandemic because there could be long-term effects that could occur in infants who are exposed to the virus during the prenatal/intrauterine period.